Distribution, diversity, endemism, and ecology of Nymphalid butterflies (Lepidoptera: Nymphalidae) in the Loxicha Region, Oaxaca, Mexico - Luis-Martínez, Armando (2022)
The Loxicha Region of Oaxaca, Mexico, has been historically important for the study of Nymphalidae, second in the Papilionoidea for species richness. Describing the diversity patterns of this butterfly clade in Loxicha can improve our understanding of the evolutionary history of the Sierra Madre del Sur, the Mexican Pacific slope, and Mexico in general. Objective: To describe the temporal and spatial patterns of Nymphalid diversity along an elevational gradient (80-2 600 m), and to compare Loxicha’s fauna with other regions in Mexico. Methods: We obtained 28 756 records from 21 sites in the Loxicha Region, representing seven years of sampling. We estimate and analyze the diversity, endemism, and distributional patterns for three elevational levels and five vegetation types. We estimated species composition and similarity with other regions of the Pacific and Atlantic slopes. Results: We identified 189 taxa, including species and subspecies, from 85 genera and ten subfamilies of Nymphalidae. Loxicha contains 46 % of the species in the family recognized for Mexico, including ten endemic species and 56 endemic subspecies. Cloud forest and low elevations were the most diverse habitats for this family. There is a clear divergence between the Atlantic and Pacific faunas, and the Sierra Madre del Sur has two faunal components. High-elevation sites in Oaxaca, and in the neighboring state of Guerrero, have a distinctive fauna, apparently isolated from low-elevation sites, revealing an archipelagic distribution for cloud forest Nymphalidae. Conclusions: The Loxicha Region is one of the richest areas for Nymphalidae in Mexico. Distribution on the Pacific slope is determined by geographical history and ecological conditions, including elevation. Nymphalidae can be used to test hypotheses of biogeographic regionalization in Mexico.